Pentingnya Pemberian Nutrisi Secara Dini Terhadap Pasien Post-Operasi Laparotomy Perforasi Ileus - Laila Sholehah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Background: Digestive surgery patients are very at risk of experiencing malnutrition, this is because the gastrointestinal tract function is not optimal. Patients who have perforated ileus really need nutrients to help reduce or cope with malnutrition. This is important because malnutrition can slow down the postoperative wound healing process. Objective: to find out more about the importance of early nutrition in patients with digestive surgery, especially in patients with ileus perforations. Methods: Using literature studies from both national and international journals by summarizing the discussion topics and comparing the results presented in the article. Results: Early nutrition will lead to faster wound recovery and healing and prevent complications from occurring so that the length of stay for patients will be shorter and will indirectly reduce costs incurred for patient treatment. Conclusion: There is an effect of early nutrition in patients after ileus perforation surgery